2016
DOI: 10.4236/jbbs.2016.613048
|View full text |Cite
|
Sign up to set email alerts
|

Doxycycline Ameliorates Schizophrenia-Like Behaviors in Experimental Models in Mice by Targeting Underlying Oxidative Stress

Abstract: Current evidences support the inhibition of oxidative and inflammatory signaling mechanisms in the treatment of schizophrenia; as cure for this disease still remains limited. Doxycycline is a tetracycline antibiotic (a minocycline congener) with strong antioxidant and anti-inflammatory properties, and better pharmacokinetic profiles. Preclinical evidence indicates that minocycline possesses antipsychotic properties. This present study was designed to evaluate the effect of doxycycline on schizophrenialike beha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…Enright, E. F., Gahan, C. G. M., Joyce, S. A., and Griffin, B. T. (2016). The impact of the gut microbiota on drug metabolism and clinical outcome.…”
Section: Effects Of Antipsychotics On the Gut Microbiome: Therapeutic...mentioning
confidence: 99%
See 1 more Smart Citation
“…Enright, E. F., Gahan, C. G. M., Joyce, S. A., and Griffin, B. T. (2016). The impact of the gut microbiota on drug metabolism and clinical outcome.…”
Section: Effects Of Antipsychotics On the Gut Microbiome: Therapeutic...mentioning
confidence: 99%
“…A recent Danish study has shown that healthcare costs for chronic SCZ is estimated to be up to 10 times higher than the cost for other chronic neurological diseases such as epilepsy or multiple sclerosis ( Hastrup et al, 2020 ); this difference in cost is explained in part by the high number of co-morbidities accompanying SCZ ( Wilson et al, 1998 ; Hennekens et al, 2005 ). However, SCZ is characterized by complex and diverse symptoms which are widely grouped into positive (e.g., hallucination, delusion, thought disorder), negative (e.g., asociality, anhedonia, amotivation), and cognitive (e.g., loss of learning and memory functions) ( Keshavan et al, 2011b ; Ben-Azu et al, 2016 , 2018a , b ; Blokland et al, 2017 ; Okubo Eneni et al, 2020 ; Ishola et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%